Principles of soil chemistry - Tan, Kim H. (Kim Howard), 1926- (Boca Raton, Fla. : CRC Press, 2011)
"Learn the secrets of soil chemistry and its role in agriculture and the environment. Examine the fundamental laws of soil chemistry, how t hey affect dissolution, cation and anion exchange, and other reactions. Explore how water can form water-bridges and hydrogen bonding, the mos t common forces in adsorption, chelation, and more. Discover how electr ical charges develop in soils creating electrochemical potentials forci ng ions to move into the plant body through barriers such as root membr anes, nourishing crops and plants. You can do all this and more with Pr inciples of Soil Chemistry, Fourth Edition. Since the first edition pub lished in 1982, this resource has made a name for itself as a textbook for upper level undergraduates and as a handy reference for professiona ls and scientists. This fourth edition reexamines the entire reach of s oil chemistry while maintaining the clear, concise style that made prev ious editions so user-friendly. By completely revising, updating, and i ncorporating a decade's worth of new information, author Kim Tan has ma de this edition as an entirely new and better book."--Publisher's descr iption.
Definitions and concepts of soil chemistry -- Overview of basic chem ical principles and units -- Soil composition and electrochemical poten tials -- Soil gas and liquid phases -- Colloidal chemistry of organic s oil constituents -- The colloidal chemistry of inorganic soil constitue nts -- Adsorption in soils -- Cation exchange -- Anion exchange -- Soil reaction -- Soil chemistry and soil formation -- Chemistry of soil-org anic matter interactions.
First ed. published 1982.
Includes bibliographical references (p. 323-342) and index.
Keywords: Soil chemistry